Pengadaan Lampu Tenaga Surya pada Panti Kemah Peduli Sahabat Kasih - Trifenaus Prabu Hidayat; Andre Sugioko; Sandra Octaviani B. Widiarto (Jurnal Pengabdian Masyarakat Charitas, 2025)
"Kemah Peduli Sahabat Kasih" is a care facility for individuals with mental disorders, managed by a single family. One of the primary challenges faced by the facility is the inadequate lighting for nighttime activities. In 2024, the team from the Faculty of Biosciences, Technology, and Innovation (FBTI) at Atma Jaya Catholic University of Indonesia contributed by installing two solar-powered lighting units: one along the access road to the facility and another for the front and back yard areas. However, these two lighting points were insufficient to fully support nighttime activities. Therefore, the 2025 community service program aimed to install additional lighting points at the Kemah Peduli Sahabat Kasih facility. The activity began with observations and interviews with the head and staff of the facility to assess conditions following the installation of the initial lighting units and to determine the additional lighting needs. It was found that three more lighting points were required, exceeding the initially allocated budget. As a result, a joint discussion was conducted between the Atma Jaya team, the facility head, and staff to decide that this year’s budget would be allocated to the purchase of solar-powered lamps. The community service program successfully procured three solar-powered lamps, which were tested and demonstrated satisfactory performance and illumination levels. The operational procedures and maintenance guidelines were also effectively communicated and understood by the facility’s head and staff.